Análise térmica da fermentação alcoólica convencional e extrativa com arraste por dióxido de carbono - Gomes, Brenda Campos (2020)
Extractive fed-batch ethanol fermentation using carbon dioxide (CO2) as striping gas has several advantages compared to the conventional fermentation, such as: reducing the effect of ethanol inhibition, allowing to use more concentrated musts, and reducing the consumption of cooling water to maintain the reactor operating temperature. In this work, different scenarios of the conventional and extractive ethanol fermentation with CO2 stripping operated in fed-batch mode were evaluated to propose improvements in the first-generation ethanol industrial production process. The mathematical models of conventional and extractive fermentation were developed based on mass and energy balances. Experimental data from bench-scale assays were used to adjust the mathematical models. Fifteen case studies were defined and simulated in the Matlab® software for 10L volume reactor based on two criteria: (1) conversion of at least 98% of substrate, and (2) minimum cooling water consumption. It was performed 227 simulation to meet the first criterion and 52 simulations to meet the second one. Comparing extractive fermentation with conventional fermentation for the total substrate concentration fed in the reactor (180 g.L-1) the cooling water consumption was reduced up to 75.6% for the CO2 flow rate of 0.4 vvm. The required CO2 flow rate was lower than that used in the literature for substrate concentrations fed into the reactor below 280 g.L-1 for the 5h feed time. The mathematical models of conventional and extractive fermentation using carbon dioxide (CO2) as striping gas were satisfactorily validated from experiments without a thermostatic bath in 2 L volume reactor. For the conventional fermentation experiment, there was an increase in temperature of the fermentation medium. In the extractive fermentation experiment, it was observed a decreasing on temperature of the fermentation medium due to ethanol removing by CO2. The results indicate that extractive fermentation has a high technical potential for industrial application, since it can contribute to the reduction of vinasse volume and steam consumption by obtaining a more concentrated wine, besides reducing the cooling water consumption and maintaining the operation temperature in the reactor. However, further studies are necessary to verify the economic feasibility of the simulated scenarios.